0634 Symptoms of insomnia and depression among individuals with Multiple Sclerosis before and during the COVID-19 – results from a prospective longitudinal study. (25th May 2022) - Sadeghi-Bahmani, Dena; Mohammadian, Youkhabeh; Piri, Nahid; Bahmani, Laleh Sadeghi; Brand, Serge; Goldstein-Piekarski, Andrea; Khazaie, Habibollah; Gross, James
Abstract: Introduction: There is some – but inconsistent – evidence that sleep and psychological health have deteriorated in the general population as a result of the COVID-19-pandemic and its related social restrictions. In the present study, we investigated whether and to what extent symptoms of insomnia, depression, fatigue, and paresthesia changed from before to during the COVID-19-pandemic among women diagnosed with multiple sclerosis (MS). Methods: A total of 90 women with MS (mean age; 37.62 (SD = 8.61) years; EDSS score: median: 2.5 (range: 0-6.50)) completed a series of self-rating scales at two time-points: Nine months before the COVID-19-outbreak in May 2019 (baseline) and during the COVID-19-pandemic (study end; 12 months after baseline: May 2020). Self-rating questionnaires covered sociodemographic and disease-related information, symptoms of insomnia, depression, fatigue, and paresthesia. Results: Symptoms of depression increased over time (medium effect size: Cohen's d = 0.53), while symptoms of insomnia (small effect size: Cohen's d = 0.43), fatigue (trivial effect size: Cohen's d = 0.19), and paresthesia (trivial effect size: Cohen's d = 0.08) did not. The only predictor for insomnia during the COVID-19-pandemic was insomnia before the COVID-19-pandemic (β = 0.36; p = 0.001); the only predictor for depression during the COVID-19-pandemic was insomnia before the COVID-19-pandemic (β = 0.66; p = 0.001). Conclusion: Overall, among a sample of female individuals with MS the COVID-19-pandemic and its related social restrictions may have had a modest influence on participants' core concerns of insomnia, depression, fatigue, and paresthesia. Support (If Any):